Edukasi Akupresur dalam Mengurangi Nyeri Haid pada Remaja Putri di Desa Cenang Kabupaten Brebes - Eka Setyawati; Ernawati; Endang Rahayu; Sari Kusmiati; Yesinta Mona Agustin; Hapsari Windayanti (Universitas Ngudi Waluyo, 2025)
Dysmenorrhea is a common menstrual disorder among adolescent girls that significantly impacts daily activities and quality of life. In Cenang Village, Brebes, most adolescents rely solely on painkillers without knowledge of non-pharmacological alternatives such as acupressure. This community service activity aimed to improve adolescents’ knowledge and skills in managing menstrual pain through acupressure techniques. A pre-experimental design with one group pretest-posttest was used, involving 30 girls aged 10–14 years. The intervention included health education and hands-on training in acupressure on specific points (LI4, SP6, PC6, and LR3). The evaluation showed a significant improvement in knowledge, from 23.3% categorized as good in the pretest to 73.3% in the posttest. The educational session was delivered through participatory and contextual methods aligned with active learning and Notoatmodjo’s theory of health promotion. The program also shifted adolescents' attitudes towards safer pain management and fostered collaboration between local health cadres, midwives, and youth. This activity proved effective and feasible to replicate in other adolescent health services (Posyandu Remaja) to enhance reproductive health literacy and self-management in rural youth communities communities. By empowering adolescents with knowledge and skills related to reproductive health, the programme not only improved their understanding but also encouraged them to take an active role in their health decisions, ultimately contributing to healthier futures for themselves and their peers. Abstrak Dismenore merupakan salah satu gangguan menstruasi yang umum dialami remaja putri dan berdampak pada aktivitas harian serta kualitas hidup. Di Desa Cenang, Brebes, sebagian besar remaja hanya mengandalkan obat pereda nyeri tanpa pengetahuan alternatif non-farmakologis seperti akupresur. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan remaja dalam mengelola nyeri haid melalui teknik akupresur. Metode yang digunakan adalah pre-eksperimental dengan desain one group pretest-posttest, melibatkan 30 remaja putri usia 10–14 tahun. Intervensi dilakukan melalui edukasi dan pelatihan langsung teknik akupresur pada titik LI4, SP6, PC6, dan LR3. Hasil evaluasi menunjukkan peningkatan signifikan pengetahuan, dari 23,3% kategori baik pada pretest menjadi 73,3% setelah posttest. Edukasi ini dilakukan secara partisipatif dan kontekstual, sesuai dengan pendekatan pembelajaran aktif dan teori promosi kesehatan menurut Notoatmodjo. Kegiatan juga berdampak pada perubahan sikap remaja terhadap penanganan nyeri haid serta membangun kolaborasi antara kader, bidan, dan remaja. Program ini terbukti efektif, aplikatif, dan layak direplikasi di posyandu remaja lainnya untuk meningkatkan pemberdayaan dan kemandirian remaja putri dalam menjaga kesehatan reproduksinya.